IDENTIFIABLE PROBLEMS INHIBITING THE EFFECTIVE MANAGEMENT OF VOCATIONAL EDUCATION PROGRAMMES IN NIGERIAN UNIVERSTITIES - Dokubo, Chidinma; Dokubo, Isaac (European Scientific Journal, ESJ, 2013)
﻿This study investigated some of the identifiable problems inhibiting the effective management of vocational education programmes in Nigerian universities. It was predicated on the assumption that vocational and technical education programmes in Nigerian universities are saddled with many problems as pointed out by Dokubo (2007) and this is directly responsible why they cannot attain the heights they envisioned as compared to their counterparts in other countries of the world. It was discovered that the Federal Government of Nigeria has made some appreciable impacts to improving the quality and standards of vocational and technical education programmes. Nevertheless, more is still required in order to meet its set objectives in the national policy on education. Onwusonye (2005) also posited that insufficient funding, lack of facilities, brain drain and inadequate number of qualified instructors and facilitators are some the factors inhibiting the implementation of vocational education programmes in most of the Nigerian universities. Therefore, it is recommended among other things that both Federal and States Governments should fund and finance vocational education adequately, more qualified instructors should be trained by encouraging more learners to enroll in the programmes, lecturers and learners should be given conducive teaching and learning climates which will enhance their maximum productivities thereby reducing the high rate of brain-drain and adequate equipment should be provided in the universities workshops/laboratories because vocational and technical education programmes are practical oriented.